What happened to the US economy during the 1918 influenza pandemic? A view through high-frequency data - François R. Velde (Federal Reserve Bank of Chicago, 2020)
Burns and Mitchell (1946, 109) found a recession of "exceptional brevity and moderate amplitude." I confirm their judgment by examining a variety of high-frequency data. Industrial output fell sharply but rebounded within months. Retail seemed little affected and there is no evidence of increased business failures or stressed financial system. Cross-sectional data from the coal industry documents the short-lived impact of the epidemic on labor supply. The Armistice possibly prolonged the 1918 recession, short as it was, by injecting momentary uncertainty. Interventions to hinder the contagion were brief (typically a month) and there is some evidence that interventions made a difference for economic outcomes.
Keywords: 330; Infektionskrankheit; Epidemie; Industrieproduktion; Insolvenz; Arbeitsangebot; Kohlenbergbau; USA